Disinflation, fiscal sustainability, and labor market adjustment in Turkey - Agénor, Pierre-Richard, 1957- 1957- (Policy research working paper, 2006)
"This paper analyzes the effects of monetary policy and fiscal adjustment on output and unemployment in Turkey. The model on which the analysis is based accounts for rural-urban migration, a large urban informal sector, flexible exchange rates, a dollarized banking system, and interactions between default risk on government liabilities, credibility, and inflation expectations. The short- and long-run effects of a rise in official interest rates and tax increases are analyzed. The results highlight the importance of accounting for the link between default risk and credibility in understanding the real and financial effects of macroeconomic adjustment. "--World Bank web site